Beyond Income: Understanding Preferences for Redistribution Among the Top 1% - Matías Strehl-Pessina; Marcelo Bergolo; Martín Leites (Institute of Labor Economics (IZA), 2025)
Do top-income individuals support different levels of redistribution compared to the rest of society? If so, what drives these differences? We address these questions using a novel dataset that combines administrative tax records with unique survey data on the social and economic preferences of workers in Uruguay. We document a marked decline in support for redistribution among the Top 1% of the income distribution. Comparing this group with the Top 50-2%, we show that differences in support for redistribution are not solely explained by current income or demographics. A set of beliefs, perceptions, and views, including political ideology, meritocratic beliefs, and views on government, account for much of the observed differences. Instead, a set of behavioral traits and social preferences, such as altruism and risk aversion, measured through incentivized online games, contribute little to explaining the gap. Finally, the differences in support for redistribution persist even when comparing the Top 1% with otherhigh-incomegroups. Together, these findings suggest that the Top 1% is a distinct group with preferences for redistribution that differ from the rest of society, even from other high-income groups.
Keywords: D31; D63; D91; H20; H30; 330; top-income individuals; preferences for redistribution; behavioral traits; social preferences; beliefs; perceptions; views